UPAYA INDONESIA DALAM MENINGKATKAN EKSPOR KOPI KE SINGAPURA TAHUN 2020-2022 - Pembasari, Tria; Pakpahan, Saiman (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2024)
This research explains Indonesia's efforts to increase coffee exports to Singapore. There is a decline in Indonesian coffee exports to Singapore in 2020-2022, namely with an export volume of 8,717.1 TON in 2019, decreasing to 5,212.9 TON in 2020 and in 2021 5,3770.0 TON, and in 2022 to 6,571.6 TON. This decline was influenced by the fact that it was in line with the Covid-19 pandemic which resulted in restrictions on exports and imports and several policies such as lockdowns, increased logistics costs and policies regarding shipping restrictions related to food production and processed foods, including coffee. The author collected data from books, academic journals, theses and internet sources related to research issues regarding Indonesia's efforts to increase coffee exports to Singapore. The author uses a liberalism perspective and the nation state level of analysis, while the theory used in this research is international trade theory. This research shows that Indonesia's strategic steps in increasing coffee exports are carried out by increasing promotion and marketing of Indonesia through the Café Asia Exhibition which aims to obtain the latest information and innovative products that can be used to meet the needs of the Singaporean coffee market as well as holding business to business sessions and coffee meetings. tasting with the aim of bringing together business people in the coffee sector and carrying out coffee taste tests so that they can adapt to market potential in Singapore. Utilization of Indonesian trade representatives in Singapore to assist export players in targeting the Singapore market and the Indonesian Government's policies in encouraging the growth of the Indonesian coffee industry, such as the People's Business Credit (KUR) program. The main aim of the KUR program is to assist coffee farmers in adopting professional coffee processing techniques. Improving the quality and quality of plantation products, especially coffee, with several strategies used by the government to overcome the problem of coffee productivity towards export. Keywords: Indonesian Coffee Exports, Singapore, and Covid-19